Hubungan Antara Penerapan Model Pencapaian Konsep Dengan Prestasi Belajar Siswa SMA Negeri 1 Manado Pada Mata Pelajaran Kimia - Rumondor, Desire Atna Sridanty; Akbar, Jakub Saddam; Polii, Henny Jeanne (Oxygenius: Journal Of Chemistry Education, 2024)
This study aims to determine whether there is a positive relationship between the application of the concept achievement model and the learning achievement of SMA Negeri 1 Manado students in Chemistry Subjects. The survey was conducted at SMA Negeri 1 Manado involving 50 respondents as a sample. Through the results of the study, it was concluded that there is a positive correlation between the application of the concept achievement model and the learning achievement of SMA Negeri 1 Manado students in Chemistry Subjects. Based on these findings, it is recommended that innovative approaches be applied in the Chemistry learning process. New and creative strategies can be introduced to improve learning effectiveness, by utilizing concept achievement models as one approach that is proven to have a positive impact.